Cooking in Other Women's Kitchens : Domestic Workers in the South,1865-1960 - Sharpless, Rebecca (Book collections on Project MUSE., 2010)
As African American women left slavery and the plantation economy behind, many entered domestic service in southern cities and towns. Cooking was one of the primary jobs they performed in white employers' homes, feeding generations of white families and, in the process, profoundly shaping southern foodways and culture.